EXTRACTION OF A RIGHT UPPER SECOND MOLAR WITH PERIAPICAL LESION: CASE REPORT - Guimarães Sampaio Trajano Dos Santos, Pedro; Cavalcanti de Lima Félix, Lucas; Alves Sarmento, José Henrique; Camillo Veras, Juliana; Coelho Travassos, Rosana Maria; Perez Leyva Ataíde, Juliana; Coelho de Ataíde Filho, Ailton; Barreto Silva , Luciano (Brazilian Journal of Implantology and Health Sciences, 2024)
ABSTRACT Objective: The objective of this case report article is to report the extraction of a second upper right molar in which there was a large periapical lesion. Methodology: During the construction of this case report, it was necessary to use the work produced by Yin (2001) as a basis, because his study teaches how the structure of a case report article should be, as well as the methodology for searching for articles, course completion, master’s and doctoral papers, which are included in this report, enriching it with proven information and scientific basis, improving this study. In order to find works related to the topic addressed and contribute with more information, searches were carried out using the following keywords: Exodontia; Periapical Lesion; Endodontics. In addition to the keywords used to acquire information relevant to the topic, searches were made in the following databases: PUBMED Central, BVS/BIREME, Scielo, Web of Science, PROSPERO in conjunction with Google Academy. Results: During the tooth removal process, there was great difficulty because it was extremely worn, fragmenting every time they tried to remove it with forceps, even the crown fragmenting. Conclusion: Odontosection was extremely useful in removing this tooth. tooth mainly because it fragments naturally due to its conditions and that after extraction, the presence of a large periapical lesion was seen, which explains the pain the patient felt in the tooth before extraction.